2011
DOI: 10.1063/1.3562589
|View full text |Cite
|
Sign up to set email alerts
|

Biaxial tensile strain effects on photoluminescence of different orientated Ge wafers

Abstract: The enhanced photoluminescence of direct transition is observed on (100), (110), and (111) Ge under biaxial tensile strain. The enhancement is caused by the increase in electron population in the Γ valley. The shrinkage of energy difference between the lowest L valleys and the Γ valley is responsible to the population increase on (100) and (110) Ge. For (111) Ge, the energy difference increases under biaxial tensile strain but the strain decreases energy difference between the electron quasi-Fermi level and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…This successful method led to the realization of light emitting sources [6][7][8] and optically pumped lasers [9] operating at 1:55 m. Similarly, direct-band-gap photoluminescence (PL) was obtained from other tensile-strained n-type Ge structures, where the strain was applied to the material using external mechanical methods [10][11][12][13].…”
mentioning
confidence: 99%
“…This successful method led to the realization of light emitting sources [6][7][8] and optically pumped lasers [9] operating at 1:55 m. Similarly, direct-band-gap photoluminescence (PL) was obtained from other tensile-strained n-type Ge structures, where the strain was applied to the material using external mechanical methods [10][11][12][13].…”
mentioning
confidence: 99%
“…The behaviour of different conduction band valleys depends on the type of strain and its orientation. In a recent study Lan et al have observed an enhancement of direct photoluminescence transitions in ntype (100), (110), and p-type (111) Ge under 0.315 % biaxial tensile strain [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, the band structure of Ge can be engineered by tensile strain: the direct bandgap decreases, the degenerate equivalent indirect valleys (X and L) shift in energy and might split, and the degeneracy of the heavy hole (HH) and light hole (LH) valence bands is lifted, depending on the type of the applied strain and its direction, as well as the substrate orientation. 1,4 Under the conventional biaxial tensile strain, Ge grown in [001] direction becomes a direct bandgap material at 1.7% strain, with about 0.2 eV reduction in energy due to the conduction band minima at Cand L-points moving downwards with respect to the vacuum level, 5 the former doing so faster. On the practical side, a moderate ($0.25%) tensile strain has been obtained in Ge grown on Si due to the difference of thermal dilatation coefficients between the two materials.…”
Section: Introductionmentioning
confidence: 99%